The Bacterial Microbiome in the Small Intestine of Hooded Seals (Cystophora cristata) - Acquarone, Mario; Salgado-Flores, Alejandro; Sundset, Monica Alterskjær (Microorganisms, 2020)
Arctic hooded seals (Cystophora cristata) are monogastric carnivores that go through extreme fasting and re-feeding in early life. They are born isolated on sea ice; suckle high-fat milk for four days and may then fast for up to one month before they start hunting and feeding on small prey (fish and crustaceans). Previous studies of the gut microbiota in pinnipeds have focused on the large intestine, while little data exist on the small intestinal microbiota. In this study, the bacterial microbiome in the proximal and distal small intestine of four captive two-year old seals (two males and two females) fed herring (Clupea harengus) was sampled post-mortem and characterized using 16S rRNA metabarcoding from the V1–V3 hypervariable region of the 16S ribosomal RNA (rRNA) genes. The seals were originally born in the wild and taken into human care at the end of the suckling period. Molecular-based analysis using Illumina Hiseq resulted in 569,910 16S rRNA sequences from the four seals (both sampling sites together). Taxonomical classification applying a naive Bayesian algorithm gave 412 Operational Taxonomic Units (OTUs). Firmicutes was the major phylum across samples (Proximal (P): 90.5% of total sequences, on average; Distal (D): 94.5%), followed by Actinobacteria (P: 7%; D: 0.3%) and Proteobacteria (P: 1.7%; D: 1.9%). Bacterial spp. belonging to the Clostridium (P: 54.1%; D: 41.6%) and SMB53 (P: 15.3%; D: 21.5%) constituted the major genera in both the proximal and distal small intestine. Furthermore, comparison with hindgut and fecal samples from geographically diverse marine mammals highlighted similarities in the microbiome between our seals and those sharing similar aquatic environments. This study has provided a first reliable glimpse of the bacterial microbiota in the small intestine microbiome of hooded seals.